The Influence of Transformational Leadership and Organizational Culture on Employee Performance at Mohammad Husni Thamrin University - Citra; Murniwati; Rivanto, Rinto; Putri, Lintang Juniar; Rahma, Fauzia; Camalia, Putri Agil (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
In the competitive era of globalization, organizations are required to continuously adapt and innovate, where the quality of human resources is a key factor for success. This study aims to analyze the influence of transformational leadership and organizational culture on employee performance at Mohammad Husni Thamrin University. The research method used is quantitative with a correlational approach. The study population was 182 permanent employees, with a sample of 33 respondents determined using the Slovin formula with a 16% error rate. Data collection techniques were carried out through distributing questionnaires with Google From, while data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression, as well as t-tests and F-tests. The results of the study indicate that transformational leadership does not have a positive and significant effect on employee performance partially. Organizational culture is also proven to have a positive and significant effect on employee performance partially. While simultaneously, both independent variables contribute significantly to improving employee performance. These findings emphasize the importance of implementing a transformational leadership style and strengthening a positive organizational culture in improving human resource performance in higher education environments. This research is expected to provide practical contributions to the management of Mohammad Husni Thamrin University in designing strategies to improve employee performance, as well as become a theoretical reference in human resource management studies, particularly regarding the role of leadership and organizational culture.